اصطلا ح "ترجمۃ القرآن " کے متعلق معاصراہل علم کی آرا ء کاتحقیقی جا ئزہ: Analytical Research on opinions of Contemporary Scholars about the Term of Quranic Translation - Zaheer Ahmad; Dr. Sana Ullah Hussain (MEI, 2023)
This article represents a critical review of different scholars about the term of “Quranic translation”. Since centuries, most of the scholars are agreed on this term and are using this. Some scholars of this “Hijra” century reject them and use the term “Meaning of Quranic Translation” and adopt such new terms. Some scholars are not agreed with them and insist upon this term “Quranic Translation” only. The base of this contradiction is upon the interpretation of the "translation". Some of them represent its lexical meaning and some of them represent its literal meaning. A great majority of the Muslim scholars give very much value to the term "Quranic Translation". Hence, they do not have contradiction in the use of modern terms and all the Muslim scholars are agreed that all the Islamic rules and regulations should be followed in “Quranic translation” in every condition.